Genotoxic evaluation of locally produced dental porcelain by using:comet assay - Kannan, T.P. (Pusat Pengajian Sains Pergigian, Universiti Sains Malaysia, 2010)
The aim of this study was to determine the genotoxicity of a locally produced dental porcelain (Universiti Sains Malaysia, Malaysia) using the Comet assay. The protocol for the Comet assay was followed as per the guidelines proposed by Tice eta!. (2000). L929 (CCL-1 A TCC, USA) mouse fibroblast cells were treated with the dental porcelain at three different concentrations (50, 100 and 200mg/ml) along with concurrent negative (Eagle's Minimal Essential Medium) and positive (Zinc sulfate) controls. DNA strand breaks were evaluated based on the mean tail moment for 150 comets/sample. There was no significant difference in the tail moment between the negative control and the different concentrations of the dental porcelain tested, suggesting that the locally produced dental porcelain did not induce any DNA damage. Also, there was no dose-dependent relationship on the tail moment. Zinc sulfate, which was used as a positive control induced significant DNA damage. The results indicate that the locally produced dental porcelain is non-genotoxic under the present test conditions